Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1534/genetics.114.168831
|View full text |Cite
|
Sign up to set email alerts
|

The TRIM-NHL Protein LIN-41 and the OMA RNA-Binding Proteins Antagonistically Control the Prophase-to-Metaphase Transition and Growth of Caenorhabditis elegans Oocytes

Abstract: In many animals, oocytes enter meiosis early in their development but arrest in meiotic prophase I. Oocyte growth, which occurs during this arrest period, enables the acquisition of meiotic competence and the capacity to produce healthy progeny. Meiotic resumption, or meiotic maturation, involves the transition to metaphase I (M phase) and is regulated by intercellular signaling and cyclin-dependent kinase activation. Premature meiotic maturation would be predicted to diminish fertility as the timing of this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
190
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(205 citation statements)
references
References 118 publications
11
190
0
Order By: Relevance
“…In lin-41 mutants pachytene cells prematurely cellularize, diplotene does not occur, and oocytes prematurely enter M phase. This premature M phase entry is elicited in part by translational derepression of a CDK-1 inhibitor (Spike et al, 2014: PMID 25261698). For further reading on oocyte maturation and oocyte release from prophase arrest, please see Control of oocyte meiotic maturation and fertilization, http://dx.doi.org/10.1895/wormbook.1.53.1, as well as (Kim et al, 2013: PMID 22872481).…”
Section: Surveillance Mechanisms During Prophase Imentioning
confidence: 99%
“…In lin-41 mutants pachytene cells prematurely cellularize, diplotene does not occur, and oocytes prematurely enter M phase. This premature M phase entry is elicited in part by translational derepression of a CDK-1 inhibitor (Spike et al, 2014: PMID 25261698). For further reading on oocyte maturation and oocyte release from prophase arrest, please see Control of oocyte meiotic maturation and fertilization, http://dx.doi.org/10.1895/wormbook.1.53.1, as well as (Kim et al, 2013: PMID 22872481).…”
Section: Surveillance Mechanisms During Prophase Imentioning
confidence: 99%
“…SS615 pgl-1(bn101) unc-24(e138) IV; pgl-3(bn104) dpy-11(e224) V, SS712 ife-1(bn127) III, WM300 alg-4(ok1041) III; alg-3(tm1155) IV, JK1403 fog-3(q470)/unc-13(e1091) lin-11(n566) I, CB3844 fem-3(e2006) IV and TH206 [ pgl-1p::PGL-1::TY1::EGFP::3xFLAG(92C12)::pgl-1 3′ UTR + Cbr-unc-119(+)] I. DG3913 lin-41(tn1541[GFP::tev::s::LIN-41]) I was kindly provided by David Greenstein (Spike et al, 2014). RNAi P-granule RNAi (simultaneously targeting pgl-1, pgl-3, glh-1 and glh-4) has been described previously (Updike et al, 2014).…”
Section: Strain Maintenancementioning
confidence: 99%
“…Then, the distribution of germ nuclei containing different numbers of RAD-51 foci in the respective zones was plotted for both N2 and cdc-25.3(ok358) mutant hermaphrodites (Fig. Nevertheless, the brood size of cdc-25.3(ok358) mutants was only 16% lower than that of N2 hermaphrodites as previously reported [43], and the embryonic lethality in cdc-25.3(ok358) mutants was merely 2.9-fold higher than that in N2 under physiological conditions (Fig. We found that the number of RAD-51 foci per germ nucleus was higher in cdc-25.3(ok358) mutant hermaphrodite gonads than in N2 hermaphrodite gonads through the pachytene zones ( Fig.…”
Section: Elevation Of Physiological Germline Apoptosis In Cdc-253 Mumentioning
confidence: 57%